Georgia : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2001)
Real GDP growth in Georgia has been slow since the Russian crisis, but there are signs of more vigorous growth, despite weak external demand. The paper discusses administrative corruption, state capture, influence, and tax policy formulation. The trends of total social expenditure in relation to fiscal adjustment have been analyzed and discussed in the context of Georgia's poverty reduction strategy. Banking sector reforms and financial development, dollarization, the energy sector, and statistical data of economic indices of Georgia are also presented.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet